2015
DOI: 10.4191/kcers.2015.52.2.92
|View full text |Cite
|
Sign up to set email alerts
|

Glass Property Models, Constraints, and Formulation Approaches for Vitrification of High-Level Nuclear Wastes at the US Hanford Site

Abstract: Current plans for legacy nuclear wastes stored in underground tanks at the U.S. Department of Energy's Hanford Site in Washington are that they will be separated into high-level waste and low-activity waste fractions that will be vitrified separately. Formulating optimized glass compositions that maximize the waste loading in glass is critical for successful and economical treatment and immobilization of these nuclear wastes. Glass property-composition models have been developed and applied to formulate glass … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 86 publications
0
19
0
Order By: Relevance
“…The Hanford Waste Treatment and Immobilization Plant (WTP) is under construction, aiming to separate the wastes into high‐volume low‐activity waste (LAW) and low‐volume high‐level waste (HLW) fractions and vitrify the wastes into separate glass waste forms . Many efforts have been devoted to maximizing the waste loading in glass, which can minimize the waste glass volume and reduce mission cost …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The Hanford Waste Treatment and Immobilization Plant (WTP) is under construction, aiming to separate the wastes into high‐volume low‐activity waste (LAW) and low‐volume high‐level waste (HLW) fractions and vitrify the wastes into separate glass waste forms . Many efforts have been devoted to maximizing the waste loading in glass, which can minimize the waste glass volume and reduce mission cost …”
Section: Introductionmentioning
confidence: 99%
“…This salt segregation and accumulation can cause processing problems, such as corrosion of refractory materials, metallic components, and facilitate volatility of hazardous components such as 99 Tc during melting . In early waste glass formulation work, the sulfur limit was set conservatively at 0.44 wt% to 1 wt% SO 3 in order to avoid potential salt accumulation …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,2 Technical challenges remain in glass formulation for economically producing durable glasses for permanent disposal. [3][4][5][6] Previous studies identified sulfur as a critical component in glass formulations because sulfur limits waste loading for many low-activity waste (LAW) glasses. [7][8][9][10][11][12] LAW is an aqueous solution containing various anions, such as NO 2 − , CO 3 2− , PO 4 3− , SO 4 2− , F − , Cl − , CrO 4 2− , and with the predominant cation Na + .…”
Section: Introductionmentioning
confidence: 99%
“…While the majority of radioactivity (~95%) is contained in the HLW, approximately 90% of the waste volume has been characterized as LAW. The waste itself, composed of 40‐60 elements, exists as water‐soluble salts and sludge …”
Section: Introductionmentioning
confidence: 99%